Asymptotic normality for the estimator of non parametric regression model under ϕ-mixing errors. Issue 14 (18th July 2017) - Zheng, Lulu; Ding, Yang; Wang, Xuejun
ABSTRACT: In this article, by using the Rosenthal-type inequality and the Bernstein's big-block and small-block procedure, we establish the asymptotic normality for the estimators of non parametric regression model based on ϕ-mixing errors. The result obtained in the article generalizes some corresponding ones for some dependent random variables.